Aberrant prefrontal cortical–striatal functional connectivity in children with primary complex motor stereotypies. (September 2021) - Augustine, Farhan; Nebel, Mary B.; Mostofsky, Stewart H.; Mahone, E. Mark; Singer, Harvey S.
Abstract: Motor stereotypies are rhythmic, repetitive, prolonged, predictable, and purposeless movements that stop with distraction. Although once believed to occur only in children with neurodevelopmental disorders such as autism, the presence and persistence of complex motor stereotypies (CMS) in otherwise typically developing children (primary CMS) has been well-established. Little, however, is known about the underlying pathophysiology of these unwanted actions. The aim of the present study was to use resting-state functional magnetic resonance imaging to evaluate functional connectivity within frontal–striatal circuits that are essential for goal-directed and habitual activity in children with primary complex motor stereotypies. Functional connectivity between prefrontal cortical and striatal regions, considered essential for developing goal-directed behaviors, was reduced in children with primary CMS compared to their typically developing peers. In contrast, functional connectivity between motor/premotor and striatal regions, critical for developing and regulating habitual behaviors, did not differ between groups. This documented alteration of prefrontal to striatal connectivity could provide the underlying mechanism for the presence and persistence of complex motor stereotypies in otherwise developmentally normal children.